Further results on Erdős–Faber–Lovász conjecture - S.M. Hegde; Suresh Dara (AKCE International Journal of Graphs and Combinatorics, 2020)
In 1972, Erdős–Faber–Lovász (EFL) conjectured that, if is a linear hypergraph consisting of edges of cardinality , then it is possible to color the vertices with colors so that no two vertices with the same color are in the same edge. In 1978, Deza, Erdös and Frankl had given an equivalent version of the same for graphs: Let denote a graph with complete graphs , each having exactly vertices and have the property that every pair of complete graphs has at most one common vertex, then the chromatic number of is . The clique degree of a vertex in is given by . In this paper we give a method for assigning colors to the graphs satisfying the hypothesis of the Erdős–Faber–Lovász conjecture and every () has atmost vertices of clique degree greater than one using Symmetric latin Squares and clique degrees of the vertices of .